Dengue hemorhagic fever associated hemophagocytc lymphohistiocytosis in primigravida: A case report - Pyrus Bhellum; Rakesh Kumar; Rishabh Bora; Bharat Kumar (Asian Pacific Journal of Tropical Medicine)
Rationale: Hemophagocytic lymphohistiocytosis (HLH) is a rare but severe complication of dengue virus infection, associated with high mortality. We report a case of a 9-week primigravida presenting with high grade fever spikes and a positive Dengue NS1 antigen. The patient exhibited worsening clinical parameters, including cytopenias. Patient concerns: A primigravida at 9th week of gestation and this condition has limited diagnostic modalities and treatment options for HLH. Diagnoses: HLH secondary to dengue hemorrhagic fever. Outcomes: Intravenous steroids were initiated with monitoring of laboratory and clinical parameters. The patient recovered successfully after initiation of intravenous steroids. Oral steroids were subsequently tapered over an next eight-week period, leading to a successful recovery. Lessons: This case is unique due to the interplay between dengue virus infection, HLH, and early pregnancy, characterized by overlapping clinical symptoms and limited treatment options. Prompt initiation of intravenous steroid therapy resulted in significant clinical improvement. This case highlights the critical importance of early identification and treatment of dengue associated HLH to reduce mortality. Furthermore, it underscores the urgent need for focused research on HLH in pregnant patients, particularly in low and middle income countries.